Nanometer‐sized extracellular matrix coating on polymer‐based scaffold for tissue engineering applications. Issue 1 (6th August 2015) - Uchida, Noriyuki; Sivaraman, Srikanth; Amoroso, Nicholas J.; Wagner, William R.; Nishiguchi, Akihiro; Matsusaki, Michiya; Akashi, Mitsuru; Nagatomi, Jiro
Abstract: Surface modification can play a crucial role in enhancing cell adhesion to synthetic polymer‐based scaffolds in tissue engineering applications. Here, we report a novel approach for layer‐by‐layer (LbL) fabrication of nanometer‐size fibronectin and gelatin (FN‐G) layers on electrospun fibrous poly(carbonate urethane)urea (PCUU) scaffolds. Alternate immersions into the solutions of fibronectin and gelatin provided thickness‐controlled FN‐G nano‐layers (PCUU FN‐G ) which maintained the scaffold's 3D structure and width of fibrous bundle of PCUU as evidenced by scanning electron miscroscopy. The PCUU FN‐G scaffold improved cell adhesion and proliferation of bladder smooth muscles (BSMCs) when compared to uncoated PCUU. The high affinity of PCUU FN‐G for cells was further demonstrated by migration of adherent BSMCs from culture plates to the scaffold. Moreover, the culture of UROtsa cells, human urothelium‐derived cell line, on PCUU FN‐G resulted in an 11–15 μm thick multilayered cell structure with cell‐to‐cell contacts although many UROtsa cells died without forming cell connections on PCUU. Together these results indicate that this approach will aid in advancing the technology for engineering bladder tissues in vitro . Because FN‐G nano‐layers formation is based on nonspecific physical adsorption of fibronectin onto polymer and its subsequent interactions with gelatin, this technique may be applicable to other polymer‐based scaffold systems for various tissue engineering/regenerative medicine applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 94–103, 2016.